Islamic Educational Leadership In Taj Al-Salatin: A Spiritual Leadership Perspective - Rahmadi Bagus Wijaya; Fatihah Nur Zahroh; Ekky Yuni Kartika; Inggi Eka Ria Mentari; Halimatus Sa'idah Muhariroh (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2026)
This study is motivated by the ethical crisis and declining integrity in contemporary leadership practices, particularly within educational and organizational contexts. The research aims to examine the concept of Islamic leadership in Taj al-Salatin and analyze its relevance to contemporary Islamic educational leadership through the perspective of spiritual leadership theory. This study employs a qualitative library research design using a Systematic Literature Review (SLR) approach. A total of 30 academic sources, including journal articles, books, and relevant scholarly publications, were systematically analyzed through thematic coding techniques consisting of open coding, axial coding, and selective coding to identify the core dimensions of leadership values in Taj al-Salatin. The findings reveal that the leadership values in Taj al-Salatin can be integrated with contemporary spiritual leadership theory through six principal dimensions: transcendence, morality and personal character, justice and trustworthiness, governance ethics, spiritual development, and leadership succession. The novelty of this study lies in constructing an integrative conceptual framework that bridges classical Islamic leadership values with modern spiritual leadership discourse within the context of Islamic educational leadership. The study contributes theoretically to the development of Islamic educational leadership studies and practically offers an ethical-spiritual leadership model applicable in Islamic educational institutions and contemporary organizations in addressing moral, ethical, and integrity crises.